MRI‐derived regional flow‐volume loop parameters detect early‐stage chronic lung allograft dysfunction. Issue 6 (27th May 2019) - Moher Alsady, Tawfik; Voskrebenzev, Andreas; Greer, Mark; Becker, Lena; Kaireit, Till F.; Welte, Tobias; Wacker, Frank; Gottlieb, Jens; Vogel‐Claussen, Jens
Abstract : Background: Chronic lung allograft dysfunction (CLAD) is a major cause for the low long‐term survival rates after lung transplantation (LTx). Early detection of CLAD may enable providing medical treatment before a nonreversible graft dysfunction has occurred. MRI is advantageous to pulmonary function testing (PFT) in the ability to assess regional function changes, and thus have the potential in detecting very early stages of CLAD before changes in global forced expiratory volume during the first second (FEV1%) occur. Purpose: To examine whether early stages of CLAD (diagnosed based on PFT values) could also be detected using MRI‐derived parameters of regional flow‐volume dynamics. Study Type: Retrospective. Population: 62 lung transplantation recipients were included in the study, 29 of which had been diagnosed with CLAD at various stages. Field Strength/Sequence: MRI datasets were acquired with a 1.5T Siemens scanner using a spoiled gradient echo sequence. Assessment: MRI datasets were retrospectively preprocessed and analyzed by a blinded radiologist according to the phase resolved functional lung MRI (PREFUL‐MRI) approach, resulting in fractional ventilation (FV) maps and regional flow‐volume loops (rFVL). FV‐ and rFVL‐based parameters of regional lung ventilation were estimated. Statistical Tests: Differences between groups were compared by Mann–Whitney U ‐test with a Bonferroni correction for multiple comparisons ( n = 2). Results: rFVL‐CC‐based parameters discriminated significantly between the presence or absence of CLAD ( P < 0.003). Data Conclusion: Using the contrast media‐free PREFUL‐MRI technique, parameters of ventilation dynamics and its regional heterogeneity were shown to be sensitive for the detection of early CLAD stages. Level of Evidence : 3 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2019;50:1873–1882.